Long-term studies on West Antarctic Peninsula phytoplankton blooms suggest range shifts between temperate and polar species - Antoni, Julieta Silvina; Almandoz, Gaston Osvaldo; Goldsmit, Jessica; García, Maximiliano D.; Flores Melo, Elizabeth Ximena; Hernando, Marcelo Pablo; Schloss, Irene Ruth (Global Change Biology)
The Western Antarctic Peninsula (WAP) experiences one of the highest rates of sea surface warming globally, leading to potential changes in biological communities. Long-term phytoplankton monitoring in Potter Cove (PC, King George Island, South Shetlands) from the 1990s to 2009 revealed consistently low biomass values, and sporadic blooms dominated by cold-water microplankton diatoms. However, a significant change occurred between 2010 and 2020, marked by a notable increase in intense phytoplankton blooms in the region. During this period, the presence of a nanoplankton diatom, Shionodiscus gaarderae, was documented for the first time. Insome instances, this species even dominated the blooms. S. gaarderae is recognizedfor producing blooms in temperate waters in both hemispheres. However, its blooming in the northern Southern Ocean may suggest either a recent introduction or a range shift associated with rising temperatures in the WAP, a phenomenon previously observed in experimental studies. The presence of S. gaarderae could be viewed as a warning sign of significant changes already underway in the northern WAP plankton communities. This includes the potential replacement of microplankton diatoms by smaller nanoplankton species. This study, based on observations along the past decade, and compared to the previous 20 years, could have far-reaching implications forthe structure of the Antarctic food web. Fil: Antoni, Julieta Silvina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Ficología; Argentina Fil: Almandoz, Gaston Osvaldo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Ficología; Argentina Fil: Goldsmit, Jessica. Fisheries and Ocean Canada; Canadá. Ministère de l'Environnement, de la Lutte ...